Annual World Bank Conference on Development Economics 2006 Growth and Integration - Bourguignon, François 1945-; Pleskovic, Boris (The World Bank, 2006)
The Annual World Bank Conference on Development Economics (ABCDE) brings together the world's leading scholars and development practitioners for a lively debate on state-of-the-art thinking in development policy and the implications for the global economy. The 17th conference was held in Dakar, Senegal, on January 27, 2005. The theme of the conference was growth and integration, which was divided into five topics: growth and integration, financial reforms, economic development, trade and development, and investment climate
Keywords: Wirtschaftswachstum; Entwicklungsländer; Konferenzschrift -- 2005 -- Dakar